House building tips (HBT) corpus dataset as a resource to discover Malay architectural ingenuity and identity - Anida Sarudin (Tanjung Malim, 2021)
House building tips (HBT) corpus dataset as a resource to discover Malay architectural ingenuity and identity by Anida Sarudin